Studi Eksperimental Kinerja Kincir Air (Water Wheel) Undershot Untuk Pembangkit Listrik Tenaga Air Pada Aliran Irigasi - Rizwan, M; Asral, Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The water flow is mostly used to generate electrical energy. The proposed research is to know the efficiency and maximum power generated by the waterwheel. In this research, the experimental method is used the water flow for irrigation, which is used to move the water wheel. The water wheel used is a type of undershot flat blade type 2 m diameter with 18 pieces of blade. The highest efficiency discharge by water wheel was 46.19 % with debit 0.313 m3/s and highest power produced water wheel 219.12 watts with debit 0.313 m3 / s. The water level greatly affects all aspects of the water wheel working system.Keywords: water wheel, undershot flat blade, efficiency